Dysregulation of hypoxia-inducible factor-1α (Hif1α) expression in the Hmox1-deficient placenta. (15th September 2020) - Zhao, Hui; Narasimhan, Purnima; Kalish, Flora; Wong, Ronald J.; Stevenson, David K.
Abstract: Introduction: Severe hypoxia exists in placentas during early pregnancy, with reoxygenation during mid-gestation. Hypoxia-inducible factor-1α (Hif1α), an oxygen sensor, initiates placental vascular development. We have shown that the placental vasculature in Hmox1 -deficient ( Hmox1 +/−, Het) pregnancies is impaired, with morphological defects similar to Hif1α -deficient placentas. Materials and methods: Whole wild-type (WT) and Het mouse placentas were collected at E8.5 (1%–3% O2 ) and E9.5–15.5 (8%–10% O2 ). mRNA levels were determined using real-time RT-PCR or PCR arrays and protein levels using Western blot. Bone marrow-derived macrophages (BMDMs) from WT, Het, and Hmox1 knockout (KO) mice, representing different Hmox1 cellular levels, were generated to study the role of Hmox1 on Hif1α ′s response to hypoxia-reoxygenation and gestational age-specific placental lysates. Results: Hif1α was expressed in WT and Het placentas throughout gestation, with protein levels peaking at E8.5 and mRNA levels significantly upregulated from E9.5–E13.5, but significantly lower in Het placentas. Genes associated with angiogenesis ( Vegfa, Vegfr1, Mmp2, Cxcl12, Angpt1, Nos3 ), antioxidants ( Sod1, Gpx1 ), and transcription factors ( Ap2, Bach1, Nrf2 ) were significantly different in Het placentas. In response to in vitro hypoxia-reoxygenation and to WT or Het placental lysates, Hif1α transcription was lower in Het and Hmox1 KO BMDMs compared with WT BMDMs. Discussion: These findings suggest that deficiencies in Hmox1 underlie the insufficient placental Hif1α response to hypoxia-reoxygenation during gestation and subsequently impair downstream placental vascular formation. Therefore, a dysregulation of Hif1α expression caused by any genetic defect or environmental influence in early pregnancy could be the root cause of pregnancy disorders. Highlights: Expression of Hif1α in wild-type (WT) placentas is gestational age-dependent. Hif1α expression is reduced in Hmox1 -deficient placentas. Expression of angiogenic genes is altered in Hmox1 -deficient placentas. Hypoxia-reoxygenation induces a differential expression of Hif1α in cells. Adding placental lysates dysregulates expression of Hif1α in Hmox1 -deficient cells.